High-yield fabrication of DNA and RNA constructs for single molecule force and torque spectroscopy experiments - Papini, Flávia S.; Seifert, Mona; Dulin, David (Nucleic Acids Research, 2019)
Single molecule biophysics experiments have enabled the observation of biomolecules with a great deal of precision in space and time, e.g. nucleic acids mechanical properties and protein-nucleic acids interactions using force and torque spectroscopy techniques. The success of these experiments strongly depends on the capacity of the researcher to design and fabricate complex nucleic acid structures, as the outcome and the yield of the experiment also strongly depend on the high quality and purity of the final construct. Though the molecular biology techniques involved are well known, the fabrication of nucleic acid constructs for single molecule experiments still remains a difficult task. Here, we present new protocols to generate high quality coilable double-stranded DNA and RNA, as well as DNA and RNA hairpins with ∼500-1000 bp long stems. Importantly, we present a new approach based on single-stranded DNA (ssDNA) annealing and we use magnetic tweezers to show that this approach simplifies the fabrication of complex DNA constructs, such as hairpins, and converts more efficiently the input DNA into construct than the standard PCR-digestion-ligation approach. The protocols we describe here enable the design of a large range of nucleic acid construct for single molecule biophysics experiments.
CRIS-Team Scopus Importer:2019-12-20

Inhibition of SARS-CoV-2 polymerase by nucleotide analogs from a single-molecule perspective - Seifert, Mona; Bera, Subhas Chandra; Van Nies, Pauline; Kirchdoerfer, Robert N.; Shannon, Ashleigh; Le, Thi-Tuyet-Nhung; Meng, Xiangzhi; Xia, Hongjie; Wood, James M.; Harris, Lawrence D.; Papini, Flavia S.; Arnold, Jamie J.; et al. (eLife, 2021)
eLife digest To multiply and spread from cell to cell, the virus responsible for COVID-19 (also known as SARS-CoV-2) must first replicate its genetic information. This process involves a 'polymerase' protein complex making a faithful copy by assembling a precise sequence of building blocks, or nucleotides. The only drug approved against SARS-CoV-2 by the US Food and Drug Administration (FDA), remdesivir, consists of a nucleotide analog, a molecule whose structure is similar to the actual building blocks needed for replication. If the polymerase recognizes and integrates these analogs into the growing genetic sequence, the replication mechanism is disrupted, and the virus cannot multiply. Most approaches to study this process seem to indicate that remdesivir works by stopping the polymerase and terminating replication altogether. Yet, exactly how remdesivir and other analogs impair the synthesis of new copies of the virus remains uncertain. To explore this question, Seifert, Bera et al. employed an approach called magnetic tweezers which uses a magnetic field to manipulate micro-particles with great precision. Unlike other methods, this technique allows analogs to be integrated under conditions similar to those found in cells, and to be examined at the level of a single molecule. The results show that contrary to previous assumptions, remdesivir does not terminate replication; instead, it causes the polymerase to pause and backtrack (which may appear as termination in other techniques). The same approach was then applied to other nucleotide analogs, some of which were also found to target the SARS-CoV-2 polymerase. However, these analogs are incorporated differently to remdesivir and with less efficiency. They also obstruct the polymerase in distinct ways. Taken together, the results by Seifert, Bera et al. suggest that magnetic tweezers can be a powerful approach to reveal how analogs interfere with replication. This information could be used to improve currently available analogs as well as develop new antiviral drugs that are more effective against SARS-CoV-2. This knowledge will be key at a time when treatments against COVID-19 are still lacking, and may be needed to protect against new variants and future outbreaks.
CRIS-Team WoS Importer:2021-10-29

Monovalent Salt Dependence of the Bacterial RNA Polymerase Open Complex Dynamics - Bera, Subhas Chandra; Seifert, Mona; Ostrofet, Eugeniu; Spermann, Monika; Papini, Flavia Stal; Malinen, Anssi M.; Dulin, David (BIOPHYSICAL JOURNAL, 2020)
CRIS-Team WoS Importer:2020-03-13

Quantitative parameters of bacterial RNA polymerase open-complex formation, stabilization and disruption on a consensus promoter - Bera, Subhas Chandra; America, Pim P. B.; Maatsola, Santeri; Seifert, Mona; Ostrofet, Eugeniu; Cnossen, Jelmer; Spermann, Monika; Stal Papini, Flavia; Depken, Martin; Malinen, Anssi M.; Dulin, David (Nucleic Acids Research, 2022)
Transcription initiation is the first step in gene expression, and is therefore strongly regulated in all domains of life. The RNA polymerase (RNAP) first associates with the initiation factor sigma to form a holoenzyme, which binds, bends and opens the promoter in a succession of reversible states. These states are critical for transcription regulation, but remain poorly understood. Here, we addressed the mechanism of open complex formation by monitoring its assembly/disassembly kinetics on individual consensus lacUV5 promoters using high-throughput single-molecule magnetic tweezers. We probed the key protein-DNA interactions governing the open-complex formation and dissociation pathway by modulating the dynamics at different concentrations of monovalent salts and varying temperatures. Consistent with ensemble studies, we observed that RNAP-promoter open (RPO) complex is a stable, slowly reversible state that is preceded by a kinetically significant open intermediate (RPI), from which the holoenzyme dissociates. A strong anion concentration and type dependence indicates that the RPO stabilization may involve sequence-independent interactions between the DNA and the holoenzyme, driven by a non-Coulombic effect consistent with the non-template DNA strand interacting with sigma and the RNAP beta subunit. The temperature dependence provides the energy scale of open-complex formation and further supports the existence of additional intermediates.
CRIS-Team WoS Importer:2022-07-22

Temperature controlled high-throughput magnetic tweezers show striking difference in activation energies of replicating viral RNA-dependent RNA polymerases - Seifert, Mona; van Nies, Pauline; Papini, Flávia S.; Arnold, Jamie J.; Poranen, Minna M.; Cameron, Craig E.; Depken, Martin; Dulin, David (Nucleic Acids Research, 2020)
RNA virus survival depends on efficient viral genome replication, which is performed by the viral RNA dependent RNA polymerase (RdRp). The recent development of high throughput magnetic tweezers has enabled the simultaneous observation of dozens of viral RdRp elongation traces on kilobases long templates, and this has shown that RdRp nucleotide addition kinetics is stochastically interrupted by rare pauses of 1-1000 s duration, of which the short-lived ones (1-10 s) are the temporal signature of a low fidelity catalytic pathway. We present a simple and precise temperature controlled system for magnetic tweezers to characterize the replication kinetics temperature dependence between 25°C and 45°C of RdRps from three RNA viruses, i.e. the double-stranded RNA bacteriophage Φ6, and the positive-sense single-stranded RNA poliovirus (PV) and human rhinovirus C (HRV-C). We found that Φ6 RdRp is largely temperature insensitive, while PV and HRV-C RdRps replication kinetics are activated by temperature. Furthermore, the activation energies we measured for PV RdRp catalytic state corroborate previous estimations from ensemble pre-steady state kinetic studies, further confirming the catalytic origin of the short pauses and their link to temperature independent RdRp fidelity. This work will enable future temperature controlled study of biomolecular complex at the single molecule level.
CRIS-Team Scopus Importer:2020-06-16

Temperature-Dependent Twist of Double-Stranded RNA Probed by Magnetic Tweezer Experiments and Molecular Dynamics Simulations - Dohnalová, Hana; Seifert, Mona; Matoušková, Eva; Klein, Misha; Stal Papini, Flavia; Lipfert, Jan; Dulin, David; Lankaš, Filip (Journal of Physical Chemistry B, 2024)
RNA plays critical roles in the transmission and regulation of genetic information and is increasingly used in biomedical and biotechnological applications. Functional RNAs contain extended double-stranded regions, and the structure of double-stranded RNA (dsRNA) has been revealed at high resolution. However, the dependence of the properties of the RNA double helix on environmental effects, notably temperature, is still poorly understood. Here, we use single-molecule magnetic tweezer measurements to determine the dependence of the dsRNA twist on temperature. We find that dsRNA unwinds with increasing temperature, even more than DNA, with ΔTwRNA = −14.4 ± 0.7°/(°C·kbp), compared to ΔTwDNA = −11.0 ± 1.2°/(°C·kbp). All-atom molecular dynamics (MD) simulations using a range of nucleic acid force fields, ion parameters, and water models correctly predict that dsRNA unwinds with rising temperature but significantly underestimate the magnitude of the effect. These MD data, together with additional MD simulations involving DNA and DNA-RNA hybrid duplexes, reveal a linear correlation between the twist temperature decrease and the helical rise, in line with DNA but at variance with RNA experimental data. We speculate that this discrepancy might be caused by some unknown bias in the RNA force fields tested or by as yet undiscovered transient alternative structures in the RNA duplex. Our results provide a baseline to model more complex RNA assemblies and to test and develop new parametrizations for RNA simulations. They may also inspire physical models of the temperature-dependent dsRNA structure.
CRIS-Team Scopus Importer:2024-02-16

The nucleotide addition cycle of the SARS-CoV-2 polymerase - Bera, Subhas Chandra; Seifert, Mona; Kirchdoerfer, Robert N.; Van Nies, Pauline; Yibulayin, Wubulikasimu; Quack, Salina; Papini, Flavia S.; Arnold, Jamie J.; Canard, Bruno; Cameron, Craig E.; Depken, Martin; Dulin, David (Cell Reports, 2021)
Coronaviruses have evolved elaborate multisubunit machines to replicate and transcribe their genomes. Central to these machines are the RNA-dependent RNA polymerase subunit (nsp12) and its intimately associated cofactors (nsp7 and nsp8). We use a high-throughput magnetic-tweezers approach to develop a mechanochemical description of this core polymerase. The core polymerase exists in at least three catalytically distinct conformations, one being kinetically consistent with incorporation of incorrect nucleotides. We provide evidence that the RNA-dependent RNA polymerase (RdRp) uses a thermal ratchet instead of a power stroke to transition from the pre- to post-translocated state. Ultra-stable magnetic tweezers enable the direct observation of coronavirus polymerase deep and long-lived backtracking that is strongly stimulated by secondary structures in the template. The framework we present here elucidates one of the most important structure-dynamics-function relationships in human health today and will form the grounds for understanding the regulation of this complex.
CRIS-Team Scopus Importer:2021-09-10
Keywords: backtracking; high-throughput/ultra-stable magnetic tweezers; nucleotide addition cycle; polymerase mechanochemistry; SARS-CoV-2 polymerase; single-molecule biophysics